Investigating cation-substituted metal vanadate photoanodes for solar water splitting - Zhang, Mengyuan (2019)
As a promising way to harvest solar energy, photoelectrochemical (PEC) water splitting has attracted intensive interest and attention in recent years. Some issues remain in the field of PEC water splitting and the choice of photoanode is an important problem. Recent decade has witnessed the rapid development of BiVO4 as one of the most successful photoanodes. While it has achieved 90% of its theoretical photocurrent, further improvement is limited by its relatively large bandgap 2.4 eV. Hence, to find alternative photoanode candidates with lower bandgap and comparable charge transport properties is urgently needed.